Selective seed layer patterning of PVD metal stacks by electrochemical screen printing for solar cell applications. (6th November 2019) - Gensowski, Katharina; Kamp, Mathias; Efinger, Raphael; Mikolasch, Gabriele; Eckert, Jonas; Bechmann, Sebastian; Weber, Ralf; Bartsch, Jonas
Abstract: A proof of principle for electrochemical screen printing (ESP) as a patterning process for thin metal stacks that can be employed, eg, in interdigitated back contact (IBC) or silicon heterojunction (SHJ) solar cells, is demonstrated. By using the ESP process, a 125 × 125‐mm 2 interdigitated back contact grid was successfully patterned into a 100‐nm physical vapor deposited (PVD) aluminum layer. Optimizations of the ESP process were performed to improve the patterning resolution. Rectangular trenches with a mean width of 36 ± 5 μm could be demonstrated on a 100‐nm–thick aluminum layer. Up to now, ESP can be applied to PVD aluminum, copper, or stacks of both materials. Finally, metal stacks of aluminum and copper were structured, which allow a more homogeneous current distribution for the ESP process and additionally for the subsequent copper electroplating because of the second metal layer underneath the layer to be structured. The successful transfer from wafer substrate to polymer foils increases the application options of ESP technology enormously, where the topography of the surface to be structured affects the printing results. Abstract : The electrochemical screen printing was successfully demonstrated on Al (100 nm)/Cu (50 nm) stacks on Si substrate by patterning a 125 × 125‐mm 2 IBC grid. This corresponds to an electrochemically etched trench length of 28.48 m, which is free of any copper residuals. The copper layer was structured locally and selectively. Following, the pattern copper seed layer was thickened by copper electroplating.